A Sliding Window Approach to Mine Negative and Positive Regular Patterns in Incremental Databases Using Vertical Data Format - V.S. Pavan Kumar, N; Rajasekhara Rao, K (International Journal of Engineering and Technology, 2018)
Incremental databases are the repositories of most emerging realistic data from ecommerce sites and other sources. They are typical in nature as new transactions are added to the database along with the progression in time. Regular patterns are more advanced and reliable as they describe not only occurrence frequency but also occurrence behavior. Finding negatively associated positive patterns is very complex process because ofÂ  search space and the size of the database. These not overlapping patterns play a vital role in decision making by extracting complex hidden knowledge from the transactional databases. Sliding window progresses with time leaving the old transactions from one end and keep on including new transactions from other end. Vertical format of database is very much handy in finding regular itemset. There was no much effort made earlier by the researchers in this area of KDD. Hence we have developed an algorithm INC_Nprism to find all the negative and positive regular itemset from incremental databases using vertical format with a sliding window. Unlike some earlier algorithms we need not construct any tree structure with this approach. Also multiple scans of database are also not required with this approach. Experimental results proved that our algorithm works efficiently and yields most satisfying results.Â Â